Gender and Patterns of Decision Making on Women with Hysterectomy - Kongvattananon, Puangpaka; Chirawatkul, Siriporn (Journal of Health Science of Thailand, 2018)
Hysterectomy is the surgical removal of a woman’s uterus and is one of most common surgical procedures that women undergo in Thailand. This qualitative study was aimed at exploring the patterns of decision making for women to undertake surgery. It also examined the meaning of “womb” as described by women with hysterectomy. Thirty six women, aged 34-73 years, who have had hysterectomy for over a year, and were living in Phra Nakhon Si Ayutthaya, a province in Central Thailand, participated in the study. Data were collected using in-depth interviews and nonparticipatory observations until saturation. Content and thematic analyses were used for data analysis. The study was conducted during July 2007-July 2008. Findings found three patterns of decision making including; 1) denial to acceptance, 2) negotiation, and 3) surrender to hysterectomy. In addition, the term “womb” is perceived in terms of conflict on whether to keep it or to have it removed. The findings also revealed that gender plays a role in the life of women with hysterectomy. It affects women’s well-being in terms of changes to the wife’s roles, negotiating power, and controlling of resources. Understanding gender perspectives and gender sensitive care of health care providers are crucial for women’s health and their needs, and to provide an appropriate long term care for women with hysterectomy.